Formulation of Papad Incorporated with Dried Palmyrah Tuber Flour - Dilani, M.A.; Mahilrajan, S.; Sinthuja, L.P. (University of Jaffna, 2021)
Papad is one of the popular and traditional snacks in Asian cuisine. Papads are highly prepared with various types of pulses, cereals, and starchy food with incorporating. Some additives. The most popular Papad is made with black gram flour with the addition of rice flour. But nowadays the price of black gram flour is more expensive. The present study was conducted on the formulation of papad using palmyrah (Borassus flabllifer L.) unboiled tuber flour (odiyal flour) instead of black gram flour and rice flour. Based on the texture of Papad using paired comparison test between the two processing methods as battered and dough, resulted the most preferable one as battered. Then experimental trials were done using battered method by altering the flour ratio of palmyrah unboiled tuber flour and fresh white rice flour. The best ratio of the formulation of Papad was identified as 1:1 in odiyal and rice flour-based on the sensory attributes such as appearance, taste, crispiness, and overall acceptability. Chemical characteristics of best formulated Papad complied with SLS 280: 2009 and has 3.02(±0.09) % of total Ash, 0.38(±0.01) % of acid insoluble ash and 0.46±0.02% of alkalinity of ash, 1.99(±0.01) % of fat, 0.155(±0.01) % of salt, 10.24(±0.16) % of total sugar and 6.22(±0.01) of pH value. There were no significant (p< 0.05) differences in moisture content, water activity, total plate count, coliform, and E. coli during the storage period of 14 days intervals up to 28 days when stored in low-density polyethylene (LDPE) at ambient temperature (28±2 oC). This study was concluded that Palmyrah unboiled tuber flour is suitable to prepare of papad with incorporating fresh white rice flour in 1:1 ratio using battered method.
Keywords: palmyrah tuber flour; papad; rice flour